Patient-reported problematic symptoms in an ALS treatment trial. Issue 3 (18th May 2016) - Raheja, Divisha; Stephens, Helen E.; Lehman, Erik; Walsh, Susan; Yang, Chengwu; Simmons, Zachary
Abstract: This study was undertaken to determine which symptoms are perceived to be most problematic for patients with ALS and how their severity changes over time. A retrospective study was performed of data from a randomized, double-blind, placebo-controlled trial of ceftriaxone in ALS. Participants completed the ALS Specific Quality of Life Instrument (ALSSQoL) at baseline and at intervals up to 96 weeks. Ten ALSSQoL items ask participants to rate how problematic symptoms are (the subjective feeling of burden of these symptoms), ranging from 0 (no problem) to 10 (tremendous problem). Six are non-bulbar (pain, fatigue, breathing, strength and ability to move, sleep, and bowel and bladder) and four are bulbar (eating, speaking, excessive saliva, and mucus). Results revealed that there were 82 subjects (56% males, mean age 53 ± 10.3 years) with ALSSQoL data for weeks 0 and 96. All 10 symptoms became more problematic over time. For non-bulbar symptoms, strength/ability to move and fatigue were the most problematic. Speaking was the most problematic bulbar symptom. In conclusion, although all the symptoms in the ALSSQoL were acknowledged as problematic, some had greater impact than others. All became more problematic over time. This should help prioritize research into symptom management, and assist individual clinicians in their approach to patient care.